1999
DOI: 10.1002/(sici)1097-0185(19990801)255:4<388::aid-ar4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

External oblique abdominal muscle: A new look on its blood supply and innervation

Abstract: Numerous reports have discussed the use of the external oblique abdominal muscle as a pedicled or a free flap for defect coverage. A detailed description of the supplying vessels and nerves is a prerequisite for successful tissue transfer but so far is not available in the literature. A study of the arteries and nerves supplying the external oblique abdominal muscle was carried out in 42 cadavers after injection of a mixture of latex and bariumsulfate. In seven fresh cadavers the motor branches were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The external oblique muscle is a Type V muscle with both dominant and multiple segmental vascular pedicles [7]. The dominant pedicles are one or two branches of either the deep circumflex iliac artery (94.7%) or the iliolumbar artery (5.3%) [8]. The segmental vascular supply is derived from the 5th through 12th posterior intercostal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The external oblique muscle is a Type V muscle with both dominant and multiple segmental vascular pedicles [7]. The dominant pedicles are one or two branches of either the deep circumflex iliac artery (94.7%) or the iliolumbar artery (5.3%) [8]. The segmental vascular supply is derived from the 5th through 12th posterior intercostal arteries.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 11 , 12 The muscle was initially thought to have a purely segmental blood supply from cutaneous perforators from the lower 8 posterior intercostal arteries. 12 With arterial injection, the studies by Kuzbari et al 9 and Schlenz et al 11 demonstrated additional significant blood supply from the deep circumflex iliac artery. The intercostal perforators to the external oblique muscle are placed along an anteriorly convex line, which curves infero-posteriorly toward the lumbar fascia from the level of the fifth rib in the mid-clavicular plane.…”
Section: Discussionmentioning
confidence: 99%
“…The motor branch to the external oblique abdominis muscle takes a similar trajectory to those of the nerves described above. The nerve branch to the external oblique abdominis muscle diverges, shortly after the parental lateral cutaneous branch appears on the surface of the body wall, and then runs on the outer fascial surface to enter the muscles from its surface (Sato, 1973;Schlenz et al, 1999). On the other hand, direct twigs innervate the internal oblique abdominis and traverse abdominis muscles from the intercostal nerve itself that runs in the deep intermuscular space.…”
Section: Three-component Modelmentioning
confidence: 99%
“…The external oblique abdominis muscle is one that belongs to the ventral outer body wall class, and receives a motor branch from the lateral cutaneous branch in the lower thoracic region (Sato, 1973;Sakamoto et al, 1996;Schlenz et al, 1999;Figure 3). No muscle in the dorsal outer body wall class is in the thoracic region.…”
Section: -1) Thoracic Regionmentioning
confidence: 99%